Review of the Chinese Hyperomias Marshall (Coleoptera: Curculionidae: Entiminae) with description of a new species - Ren, Li; Alonso-Zarazaga, Miguel A.; Zhang, Runzhi (Zootaxa, 2007)
The Chinese species of the highland weevil genus Hyperomias (Marshall, 1916) are revised. One new species, Hyperomias jiggyobensis sp. nov., is described from Jiggyob, Tibet, China. A total of 26 Hyperomias species are recorded from China. A key to Hyperomias and its related genera, a key to all Chinese Hyperomias species, and a diagnosis of each species are presented.